MP-ASI innovation emo-demo education to increase knowledge of pregnant mothers, breastfeeding mothers, and mothers of toddlers in Lokus Stunting Village, Gowa Regency - Inosenshia, Ignacia Corina; Syamsir, Nur Devi; Rachmat, Muhammad; Nilasari, Nilasari; Sahabuddin, Siti Mutmainnah Nur; Hidayanty, Healthy; Nildawati, Nildawati; Nasrah, Nasrah; Citrakesumasari, Citrakesumasari (Universitas Ahmad Dahlan, 2024)
Stunting is one instance of a failure to thrive owing to chronic malnutrition in children under five (babies under five years old). This condition is characterised by a height (TB) that is not adequate for age based on the Z-index score calculation indicator Height according to Age (TB/U zscore). Increased understanding, attitudes, and behaviour about MP-ASI innovation is the goal of this community service project for mothers under five, nursing moms, and pregnant women in Pakatto Village, Je'nemadinging, Pacellekang Village, and Panaikang Village as Locus Villages. Stunting in 2022 in Gowa Regency. Over the course of a three-week intervention, lectures, conversations, and hands-on cooking and learning activities were the mode of instruction. The Wilcoxon test was employed for data analysis. The findings showed that, in Pakatto village (P-value = 0.011) and Pacellekang (P-value = 0.011), there were differences in the knowledge of expectant mothers, nursing mothers, and mothers of toddlers before and after the MP-ASI innovation demonstration education. In the meanwhile, there was no difference in the pre- and post-MP-ASI innovation demonstration education knowledge of expectant mothers, nursing mothers, and mothers of toddlers in the villages of Je'nemadinging and Panaikang (P-value > 0.05). In order to attain even better outcomes, further empowerment initiatives must be implemented.